The Importance of Sweet Beverage Definitions When Targeting Health Policies—The Case of Switzerland - Sousa, Angelica (Nutrients, 2020)
Since high-sweet beverage intake is associated with health risks, defining what this term encompasses is relevant to the strategies confronting this problem. This study assessed both the sociodemographic factors associated with sweet beverage consumption in Switzerland and the amount consumed. According to the current definition in Switzerland (SB–CUR), sweet beverages include soft drinks, juices with added-sugar, and low-calorie sweet beverages. Using this definition and the representative menuCH survey (n = 2057; ages 18–75), the average daily sweet beverage intake was determined and compared with a new sweet beverage definition (SB–NEW), which included all beverages with free sugars and low-calorie sweeteners. A generalized linear model was used to investigate correlates of sweet beverage consumption. Sweet beverage consumption under the SB–CUR and SB–NEW definition was 240.6 g/day and 329.7 g/day, respectively, with 100% juice consumption accounting for 66% of the difference. Carbonated drinks (sodas), low-calorie sweet beverages, and 100% juices were the highest contributors, each around 60 g/day. SB–NEW intake was higher in individuals who were male, young adults (aged 18–29), from German-speaking regions, obese, or had a lower level of education. As sweet beverage consumption was much higher under the SB–NEW definition, this could have implications for health policies aimed at reducing sugar intake.